Increasing Synchronous Fire Danger in Forests of the Western United States - Abatzoglou, John T.; Juang, Caroline S.; Williams, A. Park; Kolden, Crystal A.; Westerling, Anthony LeRoy (Geophysical research letters, 2021)
Widespread fire activity taxes suppression resources and can compound wildfire hazards. We examine the geographic synchronicity of fire danger across western United States forests as a proxy for the strain on fire suppression resource availability. Interannual variability in the number of days with synchronous fire danger, defined as fire weather indices exceeding the local 90th percentile across ≥40% of forested land, was strongly correlated (r = 0.85) with the number of days with high strain on national fire management resources. A 25‐day increase in the annual number of days with synchronous fire danger was observed during 1979–2020. Climate projections show a doubling of such days by 2051–2080. Such changes will escalate the likelihood of years with extended periods of synchronous fire danger that have historically strained suppression efforts and contributed to additional burned area, therein requiring additional management strategies for coping with anticipated surges in fire suppression demands. Plain Language Summary The amount of area burned per year in forests across the western United States has been increasing over the past half‐century alongside warmer and drier weather conditions in the summer months of the western United States, called the “fire season.” These conditions lead to a number of impacts on ecosystems and society with mounting challenges for fire suppression. The occurrence of widespread fire danger and fire activity during active fire seasons has overwhelmed fire suppression resource capacity, limiting the effectiveness of managing fires and potentially increasing fire impacts. We find a strong link between fire danger days across western US forests and the number of days with high strain on national fire suppression resources. We show a 25‐day increase in the annual number of days of regionally widespread connected fire danger‐fire resource strain over the past 4 decades, and a doubling of such days by the mid‐21st century. These findings suggest that, if fuel availability, ignition patterns, and land management approaches do not substantially change over time, climate change may continue to overburden fire management efforts across the region, requiring careful strategy when fire resources are strained in future dangerous, prolonged fire seasons. Key Points Synchronous fire danger days across western US forests are interannually correlated with strain on national fire suppression resources A 25‐day increase in the annual number of days with synchronous fire danger was observed during 1979–2020 A doubling in the number of synchronous fire danger days is projected by 2051–2080